Mesangial matrix expansion in a novel mouse model of diabetic kidney disease associated with the metabolic syndrome - Elisabet Van Loon; Joseph Pierre Aboumsallem; Evelyne Lerut; Marija Bogojevic; Aleksandar Denic; Walter Park; Ilayaraja Muthuramu; Mudit Mishra; Mark Stegall; Maarten Naesens; Bart De Geest (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: The evolution of structural changes of diabetic nephropathy in human kidneys is not well documented. Instead, rodent models are used to study diabetic nephropathy in greater detail. However, all rodent models to date are subject to important limitations, and not representative for the more complex human setting where type 2 diabetes mellitus is often accompanied by the metabolic syndrome, induced by a high-fructose western diet. Objectives: To evaluate whether a novel mouse model of metabolic syndrome could be used as valid model for preclinical studies on diabetic nephropathy. Materials and Methods: We established a model of type 2 diabetes mellitus induced by a highsucrose/high-fat (HSHF) diet in female LDL-receptor knockout C57BL/6J mice and used manual morphometry to examine the renal histological changes in this model. Results: The HSHF diet induced a metabolic syndrome with weight gain, hyperinsulinemia, insulin resistance, type 2 diabetes mellitus, and hyperlipidemia. After 16 weeks on the HSHF diet, morphometric examination of kidney biopsies demonstrated increased mesangial matrix expansion, no glomerulosclerosis, and only discrete morphological changes in glomeruli. Mesangial matrix expansion was highly correlated with biological features of the metabolic syndrome. Conclusion: We describe a novel, accessible mouse model with features of the metabolic syndrome and development of mesangial matrix expansion. This model is comparable to the human setting and could serve as a relevant experimental model for nephropathy associated with type 2 diabetes mellitus. By assessing both morphological and morphometric features we demonstrated the increased sensitivity and more detailed evaluation of manual morphometry over visual estimation by light microscopy.